MODIFIED STRUCTURES AS APPROPRIATE TECHNOLOGY IN SUPPORTING THE REHABILITATION OF CORAL REEF ECOSYSTEMS IN TUAN ISLAND - Sayyid Afdhal El Rahimi; Rizwan; Ichsan Setiawan; Muhammadar; Chaliluddin; Rahmat Fadhil; Hendra Halim (CV. Naskah Aceh, 2025)
This community service program aims to support efforts to rehabilitate coral reef ecosystems on Tuan Island through the application of appropriate technology based on modified structures. Coral reefs are important ecosystems that provide habitat for various marine species, but are currently being damaged by human activities and environmental changes. In this program, we develop and apply artificial structures that have been specifically modified to support optimal coral regeneration and growth. This approach involves environmentally friendly material technology and designs that mimic natural structures, so that they can integrate well into the marine ecosystem. Through collaboration with local communities and direct training in the field, this program is expected to provide a real contribution to accelerating coral reef recovery while increasing public awareness of the importance of maintaining the sustainability of marine ecosystems.